Budget impact analysis of the use of rituximab in the treatment of rheumatoid arthritis in Italy - Benucci, Maurizio; Iannazzo, Sergio; Sabadini, Luciano (Farmeconomia. Health Economics and Therapeutic Pathways, 2009)
Objective: a Budget Impact analysis was performed to evaluate cost implications for the Italian National Health Service (NHS) of the introduction of rituximab (RTX) in the treatment of rheumatoid arthritis (RA). Methods: RA patients eligible to treatment with a second-line biologic DMARD (Disease Modifying Antirheumatic Drugs) were identified and quantified and available strategies for their management were explored. Costs associated with the different alternatives were estimated, and the impact on the NHS budget was estimated using a cohort simulation based on a Markov chain with a time horizon of 5 years and 1-year cycles. Seven alternative strategies were analyzed, each of them starting after the failure of a first anti-TNFα: 1) the use of a second and a third anti-TNFα; 2) the use of a second anti-TNFα followed by RTX; 3) the use of a second anti-TNFα followed by abatacept (ABAT); 4) the use of RTX as a second biological line, followed by an anti-TNFα; 5) the use of ABAT as a second biological line, followed by an anti-TNFα; 6) the use of RTX as a second biological line, followed by ABAT; 7) the use of ABAT as a second biological line, followed by RTX. Only direct medical costs were considered: drug acquisition, administration, incidental premedication and monitoring exams. Results: Italian patients eligible to second biological line therapies (RA patients refractory or intolerant to at least one anti-TNFα therapy) were estimated in about 650 per year. The adoption of RTX as a second line therapy produced a substantial saving in total costs (-33% at the fifth year) with respect to the strategy with RTX as third line and the one with only anti-TNFα (the last two resulting substantially cost-equivalent). The number of patients in active treatment (biologic DMARD) per unit cost resulted of about 8.1 patient-years/100,000 € with the strategy based only on anti-TNFα and increased of 10% with RTX as a third line. The strategy of RTX as a second line provided a further 41% increase (with respect to RTX as a third line). Conclusions: the introduction of RTX in the treatment of Italian RA patients represents a valuable new therapeutic option for this population especially if anticipated after a first anti-TNFα failure; it can also induce a reduction in health resources consumption for the NHS.